UNSUR DAKWAH DALAM MEMOTIVASI MAHASISWA PADA PROSES BELAJAR MENGAJAR - Masruddin Masruddin (IAIN Palopo, 2010)
This paper focused on the inserting dakwah in giving motivation during teaching and learning process. The objective of this paper is to describe the way of inserting dakwah in motivating the students during teaching and learning English process